Design of Android-Based Augmented Reality Physics Book for Grade XII of High School Chapter 9 Digital Technology - Elfisa; Safwan; Rizky Fadhillah (Jurnal Inotera, 2023)
Many senior high school students still rely on printed books for their learning, but these books often only provide 2D images with written explanations. This made Students difficult to fully ubnderstand the 3D nature of the images, especially in subjects like physic. To address this issue, the author developed an application using Augmented Reality (AR) Technology Which focused on Chapter IX of the physics textbook, mainly on "Digital Technology". This AR application students with more interesting and interactive learning experiences by showcasing animation and 3D designs. Based on he questionnaire result, from 120 students of SMK Negeri 1 Langsa it was found that 96.17% agreed that this AR app was an effective learning tool and 3.83% disagreed. So it can be concluded that this AR application can be an alternative for students and teachers as a learning media and it easier to understand, interesting, and fun in the teaching and learning process.